The Relationship between Motivation and Flow States in Sports Faculty Students - AKYOL, Pelin; İMAMOĞLU, Osman (Asian Journal of Education and Training, 2019)
The aim of this study was to investigate the relationship between motivation and flow states in sports faculty students. A total of 289 athletes who were studying at Ondokuz Mayıs University Yaşar Doğu Faculty of Sports Sciences participated in the study. Sport Motivation Scale and The Flow State Scale-2 and Dispositional Flow Scale-2 were used. T-test was used for comparisons. While there was no significant difference between the subscale scores of motivational orientation by gender (p> 0.05), a significant difference was found between the amotivation subscale (p <0.05). There was no significant difference in motivational orientation subscales between athletes doing team sports and athletes doing individual sports (p> 0.05). No significant difference was found between intrinsic and extrinsic motivation states of student athletes according to gender differences (p> 0.05). No significant difference was found between all sub-dimensions of flow state according to gender, team and individual sports (p> 0.05). T Conclusion: It can be said that motivation levels of sports educated students have an effect on flow states or flow states have an influence on motivation states. The studies that increase the flow states of the sports educated students can increase the motivation levels of the students, as well as studies that increase the motivation levels of the students can increase the flow states. Studies should be conducted in different age groups and different groups to find out in which sub-dimensions flow states and motivation states differ or are similar.